A New Method to Estimate the Cover Management Factor on the Loess Plateau in China - XIE Xinli; LI Qinglan; WANG Linhua; ZHANG Hui; WU Faqi (Shuitu Baochi Xuebao)
[Objective] To investigate the combined effect of crop cover and crop management practices on preventing soil loss and improving the accuracy of C-factor estimation. [Methods] Six millet plots with different treatments, i. e., crop plot (C1), crop-roughness plot (C2), crop-crust plot (C3), bare plot (B1), roughness plot (B2), and crust plot (B3), were established and the soil loss at four growth stage was determined under simulated rainfall. The C factor was calculated using soil loss ratio (SLR). The major factors affecting SLR were also analyzed and their correlations with SLR were then regressed through numerical simulation using MATLAB. Subsequently, the SLR estimation models designed for soil erosion prediction on the Loess Plateau could be built. Finally, the C factor could be calculated using the proposed SLR estimation model combined with the distribution curve of rainfall erosivity. [Results] Surface roughness and soil crust could reduce soil loss in crop plot. Compared with SLRcrop, SLRcrop-roughness and SLRcrop-crust were on average 21.00% and 16.50% lower, respectively. The model formulas of crop plot, crop-roughness plot, crop-crust plot were obtained, through validating by field soil and water loss data conducted in Chunhua County, the model formulas could achieve accurate prediction. The estimated C values for the whole growth stage were 0.30, 0.25 and 0.25, respectively, with the Nash coefficients being 0.96, 0.87 and 0.75, respectively. [Conclusion] The results can provide some insights for estimating C values at national scales.